Klasyfikacja osób w badaniach aktywności ekonomicznej na przykładzie Polski i Kanady - Kin-Dittmann, Irena; Mika, Ewa (Classification of persons in labour force survey on the example of Poland and Canada, 2006)
According to the recommendation of the International Labour Office (ILO) research of the professional activity in the society is carried out in a majority of countries in the world. However, the data provided by ILO are not very precise and any country can interpret them differently. As a consequence, the level of both employment and unemployment in the world scale may be unaccountable. In this paper, a classification of people engaged in economic activity has been prepared based on the data that are available both in Poland and Canada. Professional activity of women and men has been shown for the period of 1999 to 2003. Comparison of these employment and unemployment studies in Poland and in Canada has shown that there is a different approach to the subject. In Poland, the study is carried out from the point of view of utilization of existing resources and the potential of the labour force. The differences result from the various law rules utilized in Poland and in Canada. However, the differences do not alter the most important fact that employed, unemployed, or professionally inactive labour force is similar in both Polish and Canadian societies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1105, s. 53-64